3=k-9

Simple and best practice solution for 3=k-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3=k-9 equation:


k in (-oo:+oo)

3 = k-9 // - k-9

3-k+9 = 0

12-k = 0 // - 12

-k = -12 // * -1

k = 12

k = 12

See similar equations:

| (6x-12)=(x+63) | | d/6=-7 | | d/2=-6 | | w/-5=-7 | | k+1=-10 | | -7n=49 | | 5x+2=-1-2x | | -8=3(-2)+b | | 9=n+8 | | 8+m=20 | | a-9=-10 | | a+10=18 | | d+4=-8 | | 9+k=14 | | 3x-1=7x+59 | | 3n/5+9/10+n/5=-2/3/10 | | 8+m=18 | | -3=3p+7 | | 7+a=14 | | -6k=-48 | | 4=b-8 | | 9=d+4 | | d/-5=-6 | | m/-6=-1 | | 2n=-14 | | (5y-10)/(-5) | | -4=t+5 | | 8+n=13 | | m/5=-6 | | w-4=-8 | | 2[4-d+2d]=12 | | 5y-10/-5 |

Equations solver categories